A Guideline for Designing Experimental Studies in Marketing Research and a Critical Discussion of Selected Problem Areas - Koschate-Fischer, Nicole; Schandelmeier, Stephen (Journal of Business Economics, 2014)
WiSo-Import:2015-03-26:5033

Are Consumers Really Willing to Pay More for a Favorable Country Image? A Study of Country-of-Origin Effects on Willingness to Pay - Koschate-Fischer, Nicole; Diamantopoulos, Adamantios; Oldenkotte, Katharina (Journal of International Marketing, 2012)
Price-related consequences of the country-of-origin COO) cue have received limited attention in extant literature. In this study, the authors draw from equity theory and cue utilization theory and investigate 1) whether a brand's COO affects a consumer's willingness to pay and 2) the extent to which the consumer's familiarity with the brand moderates this relationship. The results of three complementary experimental studies reveal that COO indeed has a positive impact on willingness to pay. Furthermore, the authors find a negative moderating influence of brand familiarity on the COO effect in a high-involvement setting but not in a low-involvement setting. The authors discuss the theoretical and managerial implications of the findings, and they identify directions for further research. ©2012. American Marketing Association.
WiSo-Import:2015-03-26:3220
Keywords: Brand familiarity; Country of origin; Experimental research; Willingness to pay

Behavioral Pricing-Forschung im Überblick - Teil 1: Grundlagen, Preisinformationsaufnahme und Preisinformationsbeurteilung - Homburg, Christian; Koschate, Nicole (Zeitschrift für Betriebswirtschaft (Spezial Issue), 2005)
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.behavi

Behavioral Pricing-Forschung im Überblick - Teil 2: Preisinformationsspeicherung, weitere Themenfelder und zukünftige Forschungsrichtungen - Homburg, Christian; Koschate, Nicole (Zeitschrift für Betriebswirtschaft (Spezial Issue), 2005)
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.behavi_8

Brand Trust: Scale Development and Validation - Koschate-Fischer, Nicole; Gärtner, Susanne (Schmalenbach Business Review, 2015)
WiSo-Import:2015-03-26:5261

Customer Satisfaction and Elapsed Time since Purchase as Drivers of Price Knowledge - Homburg, Christian; Koschate, Nicole; Wiegner, Christian (Psychology & Marketing, 2012)
UnivIS-Import:2015-03-09:Pub.2011.rw.fbwiwi.migfk.custom

Customers' Reactions to Price Increases: Do Customer Satisfaction and the Perceived Motive Fairness Matter? - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of the Academy of Marketing Science, 2005)
Most of the previous research on price changes has focused on price decreases. This article investigates the effects of price increases at an individual level. The authors argue that customers' reactions to price increases (i.e., repurchase intentions) are strongly driven by two factors: the magnitude of the price increase and the perceived fairness of the motive for the price increase. In this context, the authors examine the role of customer satisfaction in influencing the impact of these two variables on repurchase intentions after a price increase. Their findings reveal that as satisfaction increases, the negative impact of the magnitude of a price increase is weakened. Furthermore, the results suggest that satisfaction moderates the impact of perceived motive fairness. The authors also find that the level of satisfaction can influence the valence of the perceived motives in response to a price increas
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.custom
Keywords: Customer satisfaction; Experiment; Fairness; Price increases; Pricing

Do life events always lead to change in purchase? The mediating role of change in consumer innovativeness, the variety seeking tendency, and price consciousness - Koschate-Fischer, Nicole; Hoyer, Wayne D.; Stokburger-Sauer, Nicola E.; Engling, Jan (Journal of the Academy of Marketing Science, 2018)

Do Satisfied Customers Really Pay More? A Study of the Relationship Between Customer Satisfaction and Willingness to Pay - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of Marketing, 2005)
Two experimental studies (a lab experiment and a study involving a real usage experience over time) reveal the existence of a strong, positive impact of customer satisfaction on willingness to pay, and they provide support for a nonlinear, functional structure based on disappointment theory (i.e., an inverse S-shaped form). In addition, the second study examines dynamic aspects of the relationship and provides evidence for the stronger impact of cumulative satisfaction rather than of transaction-specific satisfaction on willingness to pay.
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.dosati

Erlösmodelle für datenzentrische Dienstleistungen - Koschate-Fischer, Nicole; Ochmann, Jessica (Service Business Development: Methoden-Erlösmodelle-Marketinginstrumente, 2018)

Experimentelle Marktforschung - Koschate, Nicole (Handbuch der Marktforschung, 2008)
UnivIS-Import:2015-04-20:Pub.2008.rw.fbwiwi.migfk.experi

How Price Increases Affect Future Purchases: The Role of Mental Budgeting, Income, and Framing - Homburg, Christian; Koschate, Nicole; Totzek, Dirk (Psychology & Marketing, 2010)
This article suggests that mental budgeting processes provide a further understanding of how and to what degree price increases negatively affect a customer's future purchase behavior in a particular category of expenses. Furthermore, the authors analyze how customer income and different price presentation tactics alter this reaction. Results of two experimental studies using both students and non-students show that customer income attenuates the negative effect of a price increase on the likelihood of a future purchase in a particular expense category. As an underlying mechanism, the influence of customer income on future purchase behavior is partially mediated by the degree to which customers engage in mental budgeting. Moreover, mental budgeting strengthens the negative effect of a price increase on a future purchase in the same category of expenses, whereas it does not alter the effect of a price increase on a future purchase in another category. Finally, the framing of a price increase as a percentage versus in absolute terms leads to a lower likelihood of a future category purchase. © 2009 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2010.rw.fbwiwi.migfk.howpri

How speaking versus writing to conversational agents shapes consumer`s choice and choice satisfaction - Schindler, David; Maiberger, Tobias; Koschate-Fischer, Nicole; Hoyer, Wayne D. (Journal of the Academy of Marketing Science, 2024)

Kann Kundenzufriedenheit negative Reaktionen auf Preiserhöhungen abschwächen? Eine Untersuchung zur Rolle von Kundenzufriedenheit bei Preisanstiegen - Homburg, Christian; Koschate, Nicole (Die Betriebswirtschaft, 2003)
UnivIS-Import:2015-03-09:Pub.2003.rw.fbwiwi.migfk.kannku

Käuferverhalten - Koschate, Nicole (Lexikon der Betriebswirtschaftslehre, 2008)
UnivIS-Import:2015-04-20:Pub.2008.rw.fbwiwi.migfk.kuferv

Kundenzufriedenheit und Kundenbindung - Homburg, Christian; Koschate, Nicole (Handbuch Produktmanagement: Strategieentwicklung-Produktplanung-Organisation-Kontrolle, 2000)
UnivIS-Import:2015-04-20:Pub.2000.rw.fbwiwi.migfk.kunden

Kundenzufriedenheit und Kundenbindung - Homburg, Christian; Koschate, Nicole (Handbuch Produktmanagement: Strategieentwicklung-Produktplanung-Organisation-Kontrolle, 2002)

Kundenzufriedenheit und Kundenbindung - Homburg, Christian; Koschate, Nicole (Handbuch Produktmanagement: Strategieentwicklung-Produktplanung-Organisation-Kontrolle, 2007)

Kundenzufriedenheit und Preisverhalten-Theoretische und empirisch experimentelle Analysen - Koschate, Nicole (Gabler-Verlag, 2002)

Kundenzufriedenheit und Preisverhalten - Theoretische und empirisch experimentelle Analysen - Koschate, Nicole (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)
UnivIS-Import:2016-07-26:Pub.2002.rw.fbwiwi.migfk.kunden

Let’s face it: When and how facial emojis increase the persuasiveness of electronic word of mouth - Maiberger, Tobias; Schindler, David; Koschate-Fischer, Nicole (Journal of the Academy of Marketing Science, 2024)
Facial emojis have increasingly permeated electronic word of mouth (eWOM), but the persuasive consequences of this phenomenon remain unclear. Drawing on emotions as social information (EASI) theory, this research reveals that facial emojis influence persuasion (e.g., product choice) by affecting emotional arousal and perceived ambiguity. While the effect through emotional arousal is generally positive, the effect through ambiguity depends on the emojis’ function in eWOM: facial emojis that replace a verbal expression increase ambiguity and therefore reduce persuasion, whereas those that reiterate a verbal expression decrease ambiguity and therefore enhance persuasion. Both the emotional-arousal and ambiguity pathways determine the net persuasive effect. This research also explores two situations (high verbal context richness and eWOM from strong ties) where replacing facial emojis can increase persuasion. Finally, the authors show that facial emojis’ persuasive power is generalizable to online brand communications, influencing key management outcomes such as click-through rates for digital ads.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Electronic word of mouth; Emoji; Persuasion; Textual paralanguage

Mediation Analysis in Experimental Research - Koschate-Fischer, Nicole; Schwille, Elisabeth (Handbook of Market Research, 2021)
This chapter introduces the conceptual and statistical basics of mediation analysis in the context of experimental research. Adopting the respective terminology, mediation analysis can be referred to as an array of quantitative methods developed to investigate the causal mechanism(s) through which an independent variable influences a dependent variable. The chapter takes a regression-based approach to mediation analysis and focuses on mediation models likely to be tested in experiments (i.e., the single mediator model, parallel and serial multiple mediator models, and conditional process models). Yet, the scope of mediation analysis beyond an experimental setting will also be touched upon. Furthermore, the chapter addresses the question how to strengthen causal inference in mediation analysis through design, the collection of additional evidence, and statistical methods. It closes with a discussion of common topics of relevance when implementing mediation analysis such as sample size and power, mean centering in conditional process analysis, coding of categorical independent variables, advantages and disadvantages of a regression-based approach to mediation analysis, and software options to perform mediation analysis.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bootstrapping; Conditional process analysis; Experiments; Mediation analysis; Regression analysis

Mediation Analysis in Experimental Research - Koschate-Fischer, Nicole; Schwille, Elisabeth (Handbook of Market Research, 2018)

Menu-Based Choice Models for Customization: On the Recoverability of Reservation Prices, Model Fit, and Predictive Validity - Neuerburg, Christian; Koschate-Fischer, Nicole; Pescher, Christian (Journal of Interactive Marketing, 2021)
An increasing number of companies engage in the customization of products to reap the benefits of increased sales and the potential to charge higher prices. Online configurators, which allow customers to assemble “customized” versions of a product, play an important role in customization. In particular, they help companies learn about user preferences and generate reliable forecasts. Therefore, menu-based choice experiments have gained increased attention in recent years. Despite their high relevance, little is known about the properties of the different modeling approaches under varying study conditions. We compare four prominent modeling approaches in an extensive simulation study that systematically varies respondent heterogeneity, choice menu complexity, the available sample size, the number of individual tasks, and the underlying behavioral model. We evaluate the models for reservation price recoverability, model fit, and predictive validity. The findings show that in most cases, one obtains better results for simple and straightforward representations of respondent behavior (e.g., separate multinomial logit models for different functional areas) than for the more sophisticated modeling approaches (e.g., probit-based approaches).
CRIS-Team Scopus Importer:2020-09-04
Keywords: Customization; Menu-based choice; Monte Carlo study; Reservation price

Messung von Markenzufriedenheit und Markenloyalität - Homburg, Christian; Koschate-Fischer, Nicole; Becker, Annette (Handbuch Markenführung - Band 2, 2019)

Messung von Markenzufriedenheit und Markenloyalität - Homburg, Christian; Koschate, Nicole; Becker, Annette (Moderne Markenführung: Grundlagen-Innovative Ansätze-Praktische Umsetzungen, 2005)
UnivIS-Import:2015-04-20:Pub.2005.rw.fbwiwi.migfk.messun

Moderating Effects of the Relationship between Private Label Share and Store Loyality - Koschate-Fischer, Nicole; Cramer, Johannes; Hoyer, Wayne D. (Journal of Marketing, 2014)
WiSo-Import:2015-03-26:5092

New developments in behavioral pricing research - Koschate-Fischer, Nicole; Wüllner, Katharina (Journal of Business Economics, 2017)

On the Importance of Complaint Handling Design: A Multi-Level Analysis of the Impact in Specific Complaint Situations - Homburg, Christian; Fürst, Andreas; Koschate, Nicole (Journal of the Academy of Marketing Science, 2010)
UnivIS-Import:2015-03-09:Pub.2010.rw.fbwiwi.migfk.onthei

Preisbezogene Auswirkungen von Kundenzufriedenheit - Koschate-Fischer, Nicole (Kundenzufriedenheit: Konzepte-Methoden-Erfahrungen, 2012)

Preisbezogene Auswirkungen von Kundenzufriedenheit - Koschate-Fischer, Nicole (Kundenzufriedenheit: Konzepte-Methoden-Erfahrungen, 2015)

Preisbezogene Auswirkungen von Kundenzufriedenheit - Koschate, Nicole (Kundenzufriedenheit: Konzepte-Methoden-Erfahrungen, 2003)
UnivIS-Import:2015-04-20:Pub.2003.rw.fbwiwi.migfk.preisb

Preisbezogene Auswirkungen von Kundenzufriedenheit - Koschate, Nicole (Kundenzufriedenheit: Konzepte-Methoden-Erfahrungen, 2006)

Preisbezogene Auswirkungen von Kundenzufriedenheit - Koschate, Nicole (Kundenzufriedenheit: Konzepte-Methoden-Erfahrungen, 2008)

Psychologische Preisforschung – Ansatzpunkte für die Vermarktung technischer Gebrauchsgüter - Koschate, Nicole; Neuerburg, Christian (Die digital-vernetzte Wissensgesellschaft - Aufbruch ins 21. Jahrhundert, 2010)
WiSo-Import:2015-04-20:876
Keywords: Innovation; Forschungsbericht 2010

Security Update Labels: Establishing Economic Incentives for Security Patching of IoT Consumer Products - Morgner, Philipp; Mai, Christoph; Koschate-Fischer, Nicole; Freiling, Felix; Benenson, Zinaida (Proceedings of the IEEE Symposium on Security and Privacy (S&P), May 2020, 2020)

Shareholder value-orientiertes Preismanagement - Durch effektives Preismanagement den Unternehmenswert steigern - Koschate, Nicole; Lüers, Thomas; Fuchs, Matthias (2002)

Stichwortbeitrag "awareness set", "cause-related marketing, "cobranding", "consideration set", "corporate social responsibility", "lead user", "Marktsegmentierung", "Positionierung", "Präferenzbildung", "processed set" - Koschate-Fischer, Nicole; Liebetrau, Jennifer; Wolframm, Christiane (Dorsch-Lexikon der Psychologie, 2019)

Stichwortbeitrag "awareness set", "consideration set", "lead user", "Marktsegmentierung", "Positionierung", "processed set", "Präferenzbildung" - Koschate-Fischer, Nicole; Wolframm, Christiane (Dorsch-Lexikon der Psychologie, 2014)
WiSo-Import:2015-04-20:5240

Stichwortbeitrag "awareness set", "consideration set", "lead user", "Marktsegmentierung", "Positionierung", "processed set", "Präferenzbildung" - Koschate-Fischer, Nicole; Wolframm, Christiane (Dorsch-Lexikon der Psychologie, 2017)

The EU as Superordinate Brand Origin: An Entitativity Perspective - Diamantopoulos, Adamantios; Herz, Marc; Koschate-Fischer, Nicole (International Marketing Review, 2017)

The Role of Cognition and Affect in the Formation of Customer Satisfaction - A Dynamic Perspective - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of Marketing, 2006)
Despite the strong recognition that customer satisfaction should be viewed from a dynamic perspective, little is known about how the satisfaction judgment develops over time. Therefore, this study provides a dynamic analysis of the simultaneous influence of cognition and affect in the satisfaction formation process. The results of an experimental study based on a real consumption experience indicate that the impact of cognition on the satisfaction evaluation increases and the influence of affect decreases over time. Moreover, these effects are attenuated with inconsistent performance experiences. Finally, the study shows that the variance in customer satisfaction jointly explained by cognition and affect increases as experience accumulates. © 2006, American Marketing Association.
UnivIS-Import:2015-03-09:Pub.2006.rw.fbwiwi.migfk.therol

What if something unexpected happens to my brand? Spillover effects from positive and negative events in a co-branding partnership - Koschate-Fischer, Nicole; Hoyer, Wayne D.; Wolframm, Christiane (Psychology & Marketing, 2019)

When will Price Increases associated with Company Donations to Charity be Perceived as fair? - Koschate-Fischer, Nicole; Huber, Isabel; Hoyer, Wayne D. (Journal of the Academy of Marketing Science, 2016)

Wie reagieren Kunden auf Preiserhöhungen? Eine Untersuchung zur Rolle von wahrgenommener Fairness des Preisanstiegs und Kundenzufriedenheit - Homburg, Christian; Koschate, Nicole (Marketing-Forschung und Praxis - Journal of Research and Management, 2004)
UnivIS-Import:2015-03-09:Pub.2004.rw.fbwiwi.migfk.wierea

Willingness to Pay for Cause-Related Marketing: The Impact of Donation Amount and Moderating Effects - Koschate-Fischer, Nicole; Stefan, Isabel; Hoyer, Wayne D. (Journal of Marketing Research, 2012)
Companies increasingly employ cause-related marketing to enhance customer goodwill and improve their image. However, because these efforts have major implications for pricing strategy and firm profitability, understanding the relationship between the company's donation amount and customers' willingness to pay is important. In particular, little is known about the moderating effects that influence this relationship or their underlying mechanisms. Study 1 confirms that two types of customer predispositions moderate the link between donation amount and willingness to pay: donation-related and cause-related predispositions. Three additional studies focus on the negative moderating effect of company-cause fit and provide insights into the underlying moderation process. Specifically, the motives customers attribute to the company mediate the moderating impact of fit on the donation amount-WTP link (Study 2), which occurs particularly in cases of utilitarian (Study 3) and privately consumed products (Study 4). © 2012, American Marketing Associatio
WiSo-Import:2015-03-26:3830
Keywords: Cause-related marketing; Donation amount; Moderating effects; Willingness to pay